A role of gender in the occurrence of dimethylhydrazine induced colorectal tumors in Wistar rats - Breskvar, Ljubo (Radiology and oncology (Ljubljana), 1997)
Human colorectal carcinoma appears more frequently in males. The aim of our study was to evaluate the influence of gender on the induction of colorectal carcinoma by 1,2-dimethylhydrazine (DMH) in Wistar rats. Sixty Wistar rats (30males, 30 females) were subjected to weekly subcutanous injections of DMH (20 mg/kg) for 15 weeks. After 25 weeks from the beginning of the experiment the animals were sacrificed and autopsied. All macroscopical lesions were evaluated histologicaly. Induction of colorectal tumors succeeded in 37% of males and 17% of females. There were 21 tumors of the large bowel found, of these 15 in males and 6 in females. Histologically, males had 11 adenomas, 2 signet-cell carcinomas and 2 adenocarcinomas, while females had 4 signet-cell carcinomas and 2 adenomas. We also found extracolonic tumors, mainly those of the small intestine and of the Zymbal glands. Wistar rats showed lower incidence of DMH-induced colorectal tumors in comparison with other strains ofrats. The gender-dependent difference in the incidence of colorectal tumors was found to be statistically marginally significant (p<0.08), whereas the difference in the incidence of all induced tumors between genders was significant (p<0.02). Males showed a greater incidence of coloreactal tumors and also a greater histological resemblance to human colorectal tumors than females. That is why we recommend Wistar males rather than females for research on colorectal tumors.
Keywords: debelo črevo; poskusi na živalih; rak (medicina)